2022
DOI: 10.2147/rmhp.s358641
|View full text |Cite
|
Sign up to set email alerts
|

A 25-Year Trend of Catastrophic Health Expenditure and Its Inequality in China: Evidence from Longitudinal Data

Abstract: Purpose The Chinese government has carried out two major cycles of reform to improve the health system and reduce the disease burden on residents. This study aims to comprehensively track the trends in the occurrence of catastrophic health expenditure (CHE) and its inequality in the past 25 years, which may help better understand the influence of health system reforms on CHE and its inequality. Methods The study employed the subset of data from China Health and Nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…These results remained robust when using other thresholds (results available upon request). Existing literature also found that residency, income, and household family size were correlated with the incidence of CHE and MI [ 9 , 13 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results remained robust when using other thresholds (results available upon request). Existing literature also found that residency, income, and household family size were correlated with the incidence of CHE and MI [ 9 , 13 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results were comparable with findings from previous studies using other data sources. 8 , 39 Fig. 1 shows the provincial variations in the incidence of CHE and MI in 2017.…”
Section: Resultsmentioning
confidence: 99%
“… 8 Another study using data from the China Health and Nutrition Survey applied total net household income as the denominator, and showed that the incidence of CHE using the 40% threshold was around 9% in 2015. 39 All these estimates suggest large margins for improvements in financial protection in China, although China has achieved laudable progress during the past 20 years. More importantly, we found large variations in financial risk protection within the nation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a potential solution to decrease the burden of paying for OOPE is to consider through universal health insurance [1,2]. The effect of health system nancing on the welfare of households, mainly those economically disadvantaged, has in uenced the development of health systems and insurance mechanisms in various countries, such as the USA, Australia, India, and Indonesia [25]. In order to achieve universal health coverage (UHC), it is essential to rely on prepaid health spending and pool nancial risks.…”
Section: Discussionmentioning
confidence: 99%